2001
DOI: 10.1159/000056088
|View full text |Cite
|
Sign up to set email alerts
|

Acute Antidepressant-Like and Antianxiety-Like Effects of Tryptophan in Mice

Abstract: The antidepressant-like, antianxiety-like and sedative effects of tryptophan (TRP), in the absence and presence of p-chlorophenylalanine (p-CPA), and melatonin were studied in mice using the forced-swimming test, open-field test and activity cage, respectively. Single-dose TRP caused an antidepressant-like effect dose dependently up to 125 mg/kg. No significant effect was observed, however, when the TRP dose was increased to 250 mg/kg, i.e. a reversal of effect occurred at high dose. With p-CPA pretreatment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 31 publications
3
30
1
Order By: Relevance
“…Previous studies reported no effects of PCPA or the serotonergic neurotoxin 5,7-dihydroxytryptamine on immobility time in mice and rats Borsini, 1995;Redrobe et al, 1998;Page et al, 1999). Likewise, doses of TRP close to that we used had no effect on immobility time in NIH-Swiss mice, whereas at 50 -125 mg/kg TRP reduced immobility (Hilakivi-Clarke et al, 1990;Wong and Ong, 2001).…”
Section: Discussioncontrasting
confidence: 48%
“…Previous studies reported no effects of PCPA or the serotonergic neurotoxin 5,7-dihydroxytryptamine on immobility time in mice and rats Borsini, 1995;Redrobe et al, 1998;Page et al, 1999). Likewise, doses of TRP close to that we used had no effect on immobility time in NIH-Swiss mice, whereas at 50 -125 mg/kg TRP reduced immobility (Hilakivi-Clarke et al, 1990;Wong and Ong, 2001).…”
Section: Discussioncontrasting
confidence: 48%
“…Our study has the advantage of following the TRP effect over several weeks. It is consistent with the report of Wong and Ong [23], reporting an antidepresssive-like effect of a single dose of TRP in mice, such effect is dose-dependent. In the same species, the reduction of immobility by TRP in Porsolt's swim test has been also reported suggesting that TRP has antidepressant-like properties [45].…”
Section: Discussionsupporting
confidence: 93%
“…In support of this, report of Wong and Ong [23] in mice who reported that MEL caused an antidepressant-like less potent than TRP was referred, such effect was due to its conversion to 5-HT. Also, TRP supplementation provoked a significant rise in the levels of brain 5-HT in many animal species [53,64,65].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations